PENGARUH CURRENT RATIO DAN TOTAL ASSET TURNOVER TERHADAP HARGA SAHAM PADA PT ULTRAJAYA MILK TBK PERIODE 2013-2022 - Nuriyah, Adinda; Sairin (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the Current ratio and Total Asset Turnover on Share Prices at PT Ultrajaya Milk Tbk for the 2013-2022 period. The research method used is a descriptive method with a quantitative approach. The population in this research is the financial report of PT Ultrajaya Milk Tbk. The results of this research indicate that partially the Current ratio does not have a significant effect on share prices at PT. Ultrajaya Milk Tbk. This is proven by the results of the tcount value being smaller than ttable (-0.340 < 2.364) and significant at 0.744 > 0.05. Total Asset Turnover has a significant positive effect on share prices at PT. Ultrajaya Milk Tbk. This is proven by the results of the tcount value being greater than ttable (3.167 > 2.364) and significant 0.016 < 0.05. Simultaneous Current ratio and Total Asset Turnover together have a significant effect on the share price at PT. Ultrajaya Milk Tbk. This can be proven from the results obtained Fcount 5,018>Ftable 4.74 and significantly smaller than 0.05, namely .044b<0.05.